Analisis Tingkat Kesantunan Berbahasa dalam Tuturan Guru dan Peserta Didik dalam Kegiatan Pembelajaran Bahasa Indonesia di SMP PGRI Jekulo Kudus - Ali Asfuri (AL-BURHAN, 2022)
This study discusses the politeness of language in the speech of teachers and students in the Indonesian language learning process at SMP PGRI Jekulo Kudus. The focus of this research is in the form of words and sentences that contain compliance with the principles of politeness and violations of the principles of politeness in the language of teachers and students. This study aims to describe the application of the language politeness principle in the Indonesian learning process, and describe the violation of the language politeness principle in the Indonesian language learning process at SMP PGRI Jekulo Kudus. This research approach is a qualitative approach, while the type of research is ethnometodology which is oriented towards conversational analysis. The data is obtained directly by recording the dialogue or speech of the teacher and students during the teaching and learning process. After the data was collected, data analysis was carried out in the form of politeness. The data analysis activity begins with selecting data that is suspected of being a form of speech that embodies the principle of politeness and violations of the principle of politeness. Then the data collection is classified based on the Leech politeness maxims as language politeness rules.